Agricultural Waste Processing Technologies (Silage and Ammoniation) for Ruminant Feed in Drylands: Literature Review - Nitty Cendrabagusti Mafefa; Adyanto Nessy Banamtuan (Journal of Tropical Animal Science and Technology, 2026)
Dryland regions commonly experience ruminant feed shortages during the dry season. The year‑round availability of high‑quality feed is a critical prerequisite for sustainable livestock development. Livestock productivity can be improved through the consistent provision of nutritionally adequate feed resources. This opportunity is supported by abundant agricultural production, particularly maize, which has not yet been optimally utilized for livestock feeding. However, most existing feed resources are characterized by low nutritional value and therefore cannot adequately support animal productivity without further processing. Agricultural residues such as rice straw and corn stover are available in large quantities but require technological intervention to improve their feeding value. Processing technologies based on silage and ammoniation have been widely reported to enhance nutrient availability and extend the storage life of these materials. This review synthesizes published research on the potential of agricultural residues as ruminant feed resources in dryland ecosystems and evaluates the effectiveness of silage and ammoniation technologies. The evidence indicates that both technologies substantially improve feed quality, increase feed availability during the dry season, and strengthen farmers’ capacity to utilize local resources in a sustainable livestock production system.